Consumer Preferences for Online Food Delivery Order Services in DKI Jakarta (Case Study of Go-Food and Grabfood) - Amri Usmi (Sharia Agribusiness Journal, 2022)
The purpose of this study was to determine the characteristics of online food delivery consumers in DKI Jakarta and to determine the preferences of online food delivery consumers in DKI Jakarta. This research was conducted in DKI Jakarta covering 5 areas, Jakarta South, Central, East, West, and North Jakarta. The method used for data collection in this research is to use a survey method using a questionnaire tool to collect respondent data, with the respondents' criteria being 1) people living in DKI Jakarta or working in DKI Jakarta, 2) using GoFood and/or GrabFood, 3) aged 16-64 years. The analytical technique used is the Friedman test approach to see the order of attributes that are the priority of OFD consumers in DKI Jakarta. The results of the analysis in this study show that women are 55% and men 45%, the age range is dominated by 16-25 years, with high college education, private employment, and income of 4 million-10 million. The results of the priority attributes of OFD consumers in sequence are Price, Promotion, Time & Delivery, ease of application, halal label, consumer privacy, payment method, restaurant diversification, and restaurant location.Keywords: preference; online food delivery;  Friedman test        AbstrakTujuan dari penelitian ini adalah untuk mengetahui karakteristik konsumen pesan antar makanan online di DKI Jakarta dan untuk mengetahui preferensi konsumen pesan antar makanan online di DKI Jakarta. Penelitian ini dilakukan di DKI Jakarta yang meliputi 5 wilayah, Jakarta Selatan, Pusat, Timur, Barat, dan Jakarta Utara. Metode yang digunakan untuk pengumpulan data dalam penelitian ini adalah menggunakan metode survei dengan menggunakan alat kuesioner untuk mengumpulkan data responden, dengan kriteria responden 1) orang yang tinggal di DKI Jakarta atau bekerja di DKI Jakarta, 2) menggunakan GoFood dan/atau GrabFood, 3) usia 16-64 tahun. Teknik analisis yang digunakan adalah pendekatan uji Friedman untuk melihat urutan atribut yang menjadi prioritas konsumen OFD di DKI Jakarta. Hasil analisis dalam penelitian ini menunjukkan bahwa perempuan 55% dan laki-laki 45%, rentang usia didominasi 16-25 tahun, dengan pendidikan tinggi perguruan tinggi, pekerjaan swasta, dan pendapatan 4 juta-10 juta. Hasil atribut prioritas konsumen OFD secara berurutan adalah Price, Promotion, Time & Delivery, kemudahan aplikasi, label halal, privasi konsumen, metode pembayaran, diversifikasi restoran, dan lokasi restoran.Kata Kunci: pilihan; pengiriman makanan online; uji Friedman